Penggunaan Banner “Cegah Stunting” Sebagai Upaya Pengurangan Angka Stunting di Kelurahan Cigugur Tengah - Rinda Cahyani; Erin Volosa (Universitas Tanjungpura, 2023)
The problem of stunting in Indonesia is a problem that has become a national concern. The target to reduce stunting in 2024 is 14%, while in 2022 it will still be 24%. Various efforts to deal with stunting have been carried out by the Indonesian Government, both at the central and regional government levels, but have not been able to reduce stunting significantly. This Field Work Lecture activity is aimed at identifying cases of stunting in Cigugur Tengah Village and carrying out interventions. This activity uses a mixed method with the type of Sequential Explanatory Design. The participants in this activity were the people of Cigugur Tengah Village with the main target being toddlers and their parents. The results showed that there were 339 infants and toddlers in Cigugur Tengah Village who were identified as stunting. The problem of stunting in Cigugur Tengah Subdistrict is caused by various factors, one of which is the lack of education and knowledge of the community, especially prospective parents and parents regarding nutrition and the dangers of stunting. The efforts of KKN students to prevent stunting cases are by using a standing banner that carries the theme